2021
DOI: 10.1212/nxi.0000000000001004
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes From Subjects With Multiple Sclerosis Express EBV-Derived Proteins and Activate Monocyte-Derived Macrophages

Abstract: ObjectiveTo investigate in a cross-sectional study the effect of serum-derived exosomes on primary human blood monocyte-derived macrophages (MDMs) comparing exosomes from healthy donors vs patients with relapsing-remitting multiple sclerosis in remission and in relapse and to assess whether the response correlates with exosomal Epstein-Barr virus (EBV) protein expression.MethodsA total of 45 serum-derived exosome preparations were isolated from patients and healthy controls and verified for the expression of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
0
21
1
1
Order By: Relevance
“…In naive PBMCs, the data suggest an increase in protein levels and transcription of IFN-γ after co-cultivation with EV tax+ HBZ+, though this is not statistical significant. Recent studies have shown that EVs are able to induce a pathogen-specific response in immune cells in studies regarding Salmonella typhimurium (Hui et al, 2021 ), human immunodeficiency virus (Sampey et al, 2016 ), hepatitis B virus (Kouwaki et al, 2016 ), and Epstein-Barr virus (Mrad et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In naive PBMCs, the data suggest an increase in protein levels and transcription of IFN-γ after co-cultivation with EV tax+ HBZ+, though this is not statistical significant. Recent studies have shown that EVs are able to induce a pathogen-specific response in immune cells in studies regarding Salmonella typhimurium (Hui et al, 2021 ), human immunodeficiency virus (Sampey et al, 2016 ), hepatitis B virus (Kouwaki et al, 2016 ), and Epstein-Barr virus (Mrad et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results found in this study revealed that the expression of latent membrane proteins LMP1 and 2A and EBV nuclear antigen EBNA1 was higher on exosomes derived from patients with active MS compared with healthy controls and stable patients. Moreover, MDMs differentiated from patients with active disease were better secretors of CXCL10, CCL2 and CXCL9, than MDMs from healthy and stable MS groups (147). Thus, the authors suggest that EBV(+) exosomes could promote a proinflammatory response in MS patients by antigen-presenting cells and may contribute to ongoing immune activation.…”
Section: Evs In Multiple Sclerosismentioning
confidence: 92%
“…Monoclonal MBP-specific antibodies in MS patients interact with EBV encoded LMP1 to suppress CD4 + T cell activation, leading to elevated antibody concentrations against CTARs and the development of MS ( Lomakin et al, 2017 ). In addition, exosomes containing viral proteins (LMP1) from EBV-infected human oligodendrocyte lines were found to reduce MBP expression and promote demyelination ( Sampey et al, 2014 ; Wu et al, 2020 ; Mrad et al, 2021 ). EBV-encoded membrane protein LMP2A in B cells is abnormally sensitive to TLR9 activation.…”
Section: Ebv and Multiple Sclerosismentioning
confidence: 99%